Love Scamming Di Era Digital Perlindungan Hukum Dan Tantangan Dalam Penanganan Kasus Love Scam Di Aplikasi Kencan Di Indonesia - Soleha Liliani Malik; Fakhris Lutfianto Hapsoro (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study analyzes the legal framework surrounding cybercrime related to love scams perpetrated through social media in Indonesia. Love scamming has emerged as a significant issue, particularly among young adults using dating applications. The research highlights the lack of specific legal regulations addressing love scams, despite existing laws on cybercrime. Through normative research methods, the study examines the challenges faced by victims in seeking justice and the inadequacies in legal protections available to them. The findings indicate that many victims do not report incidents due to feelings of shame and fear of stigma, leading to a lack of data on the prevalence of such crimes. The journal calls for improved legal frameworks and greater public awareness to protect individuals from falling victim to love scams.